First, let’s try to isolate the variable x, or get x alone on one side of the equation. One of the x terms is inside the parentheses on the right. So, let’s start by getting rid of the parentheses to make this equation easier to work with. One way to do this is to distribute the 5 to the x and to the 3. You can think of this as (5·x)+(5·3). Rewrite the right side.

6x+3 = 5(x+3)
6x+3 = ? + ?

1 answer

To rewrite the right side of the equation \( 6x + 3 = 5(x + 3) \) by distributing the 5, we will apply the distributive property:

\[ 5(x + 3) = 5 \cdot x + 5 \cdot 3 \]

This gives us:

\[ 5x + 15 \]

Now, we can rewrite the equation:

\[ 6x + 3 = 5x + 15 \]

So we have:

\[ 6x + 3 = 5x + 15 \]

In summary, the rewritten right side is \( 5x + 15 \).